Necesidad de establecer nuevas medidas de sanciones de prision, en relacion al trafico de las especies exóticas y silvestres de conformidad con lo que establece el articulo 247, del código orgánico integral penal del Ecuador - Criollo Chávez, Ana Lucía (2017)
The Criminal Code of Integral typifies and categorized as crimes against flora and fauna, those administrative lack previously the only sanctioned with fines or environmental violations. Crimes against flora and fauna responds to sensitivity to the environment, particularly harmful, conscious and voluntary acts against certain species that are protected in territories and outdoors, where their removal or destruction produces an ecological imbalance and means a risk to the environment. The second paragraph of Article 14 of the Constitution of the Republic of Ecuador, guarantees that: "It is of public interest environmental preservation, conservation of ecosystems, biodiversity and integrity of the genetic heritage of the country, prevention environmental damage and the recovery of degraded natural areas." The foundation of the offense against the flora and fauna is because the State considers the public interest, that the purpose of the State's actions must be good in the protection and preservation of the environment. The governing verbs crime of flora and fauna listed in Art. 247 of the Code Integral Penal are those of hunting, fishing, capture, collect, extract, have, transport, traffic, benefit, exchange or market, in their specimens or portions thereof, its constituent parts, products and derivatives of flora and fauna that lead to a hazard or extinction crime is to preserve the diversity and purity of species, thus preventing ecological imbalance and a risk to the environment ambient. But within this trafficking of species, there are some exotic and wild called, that being original is unique in the world, for the price and value in its illegal marketing, must be set rigidly penalties of deprivation of liberty, as it is a crime committed against the biodiversity that our country possesses, ie that has given importance to the protection of our ecosystem. This legal research deals with an important and topical legal problems, which should be taken into account so that it complies with rigor of the law with prison sentences and to protect the environmental heritage of our country, respecting and enforcing the laws. With this brief description of the issues raised in this investigation, I think it is important to analyze the fourth chapter of Crimes against the environment and nature or Pacha Mama, specified in Article 247 of the Code Integral Penal, and included offenses relating to trafficking fauna of exotic and wild species throughout the national territory, as a new criminal conduct this activity is divided into two main groups, the first trade and illegal sale of live wild species with the to be offered to people who want to have them at home as pets. The second is the sale of derivatives or products of wild species such as: ortos stuffed animals, parts of animals, fur, feathers, hides and. Because of this situation is a priority and essential that laws allowing first define the crime and secondly penalize this illegal and contribute to current, clear and strong criminal laws that punish the person or persons engaged in trafficking in innocent lives is believed . This in one way or another guaranteed as a right to freedom stated in Art. 66 paragraph 27 of the Constitution of the Republic of Ecuador, the right to live in a healthy, ecologically balanced, pollution-free and in harmony with nature .